Introductory note on Emergent Unconscious Knowledge Networks (Asygnodic Networks) - Edward M. Roche; Michael J. Blaine; Henry Bakis (Netcom)
This note introduces the following paper on the concept of Emergent Unconscious Knowledge Networks (Asygnodic Networks) created by E. Roche and M. Blaine. The concept of asyngnosis explains a large number of diverse phenomena involving organizations, groups and decision making. It will present the genesis and definition of Asygnodic Networks and will focus on how they raise challenges to traditional theories of decision making and emerging social networks.